Rational synthesis of atomically precise graphene nanoribbons directly on metal oxide surfaces - Kolmer, M.; Steiner, Ann-Kristin; Izydorczyk, I.; Ko, W.; Engelund, M.; Szymonski, M.; Li, A. P.; Amsharov, Konstantin (Science, 2020)
Atomically precise graphene nanoribbons (GNRs) attract great interest because of their highly tunable electronic, optical, and transport properties. However, on-surface synthesis of GNRs is typically based on metal-surface assisted chemical reactions, where metallic substrates strongly screen their designer electronic properties and limit further applications. Here, we present an on-surface synthesis approach to forming atomically precise GNRs directly on semiconducting metal oxide surfaces. The thermally triggered multistep transformations preprogrammed in our precursors' design rely on highly selective and sequential activations of C-Br, C-F bonds and cyclodehydrogenation. The formation of planar armchair GNRs terminated by well-defined zigzag ends is confirmed by scanning tunneling microscopy and spectroscopy, which also reveal weak interaction between GNRs and the rutile TiO2 substrate.
CRIS-Team Scopus Importer:2020-07-10